Dapagliflozin reduces systolic blood pressure and modulates vasoactive factors. Issue 7 (11th April 2021) - Ghanim, Husam; Batra, Manav; Green, Kelly; Hejna, Jeanne; Abuaysheh, Sanaa; Makdissi, Antione; Chaudhuri, Ajay; Dandona, Paresh
Abstract: Aim: To investigate the mechanisms underlying improvements in blood pressure (BP) and congestive heart failure outcomes following treatment with dapagliflozin, a sodium‐glucose co‐transporter‐2 inhibitor. Research Design and Methods: A total of 52 patients with type 2 diabetes (T2D) with an HbA1c of less than 8% participated in this prospective, double‐blind and placebo‐controlled study. Patients were randomized (1:1) to either dapagliflozin 10 mg daily or placebo for 12 weeks. Half the patients were also monitored for 6 h following their first dose for acute effects on BP. Blood and urine samples were collected and levels of angiotensinogen, angiotensin II, renin, aldosterone, endothelin‐1, atrial natriuretic peptide (ANP), brain natriuretic peptide, cyclic adenosine monophosphate, cyclic guanosine monophosphate (cGMP) and neprilysin were measured. The expression of angiotensin‐converting enzyme, guanylate cyclase and phosphodiesterase 5 (PDE5) was measured in circulating mononuclear cells (MNC). Results: A total of 24 and 23 patients receiving dapagliflozin and placebo, respectively, completed the 12‐week study. Systolic BP decreased significantly, compared with placebo, both after single‐dose (by 7 ± 3 mmHg) and 12‐week (by 7 ± 2 mmHg) treatment with dapagliflozin. Dapagliflozin suppressed angiotensin II and angiotensinogen (by 10.5 ± 2.1 and 1.45 ± 0.42 μg/mL, respectively) and increased ANP and cGMP (by 34 ± 11 and 29 ± 11 pmol/mL, respectively) compared with the placebo group. cGMP levels also increased acutely following a single dose of dapagliflozin. Dapagliflozin also suppressed PDE5 expression by 26% ± 11% in MNC. There were no changes observed in the other vasoactive mediators investigated. Conclusions: Dapagliflozin administration in T2D resulted in both acute and chronic reduction in systolic BP, a reduction in vasoconstrictors and an increase in vasodilators. These changes may potentially contribute to its antihypertensive effects and its benefits in congestive cardiac failure.